Effects of cognitive-behavioural intervention programme on the anxiety level and performance of gymnasts in a competitive environment - Smyth, P.; Masterson, L.; Kearney, P. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
This study arouse out of the concern of a gymnastics coach that her gymnasts were underperforming in competition due to anxiety. The purpose of the study was to assess the effects of a cognitive-behavioral intervention programme on performance, anxiety and confidence in the competitive sport environment. Methods: Ten female gymnasts aged 12-17 yrs were pre-tested in a competitive sport environment for state anxiety and self confidence on the CSAI-2 test (Martens et al., 1990) and on balance beam performance. The competitive environment included an udience made up of parents, gymnasts, "march on" music and two qualified judges who scored performances. At a gymnastic camp on the following week all gymnasts underwent training which included practice on the balance beam. In addition half of the group underwent cognitivebehavioral training based on Suinn`s (1994) visual motor behavior rehearsal (VMBR) programme. The other half of the group did not undergo this training and acted as a control. VMBR combines muscle relaxation, controlled breathing and use of mental imagery to visualise a relaxed scene, a successful competition scene previously experienced and an upcoming competition scene. As manipulation checks, gymnasts were asked to rate clarity of images, levels of relaxation and the feel of imaged movements. They were also asked to practice the procedures at home and to record comments in a log which would be discussed at the beginning of the next session. Participants were retested at the end of the week and again one week later (retention) in the same competitive environment as the pre-test. Results: The intervention group showed significant improvements in performance on the balance beam along with reduced cognitive and somatic anxiety and increased confidence. The control group showed no improvements in performance and no changes in anxiety and confidence. Discussion: The findings provide support for the effectiveness of a psychological intervention programme for controlling anxiety and enhancing confidence and performance in competitive sport situations. There is also support for incorporating psychological training into the physical practice of skills and for involving young performers more intimately in their psychological training. One limitation of the study however is that the possibility of a placebo effect was not controlled for.